MacArthur Competence Assessment Tool for Treatment in Alzheimer disease: cross-cultural adaptation - Raquel Luiza Santos; Maria Fernanda Barroso de Sousa; José Pedro Simões Neto; Elodie Bertrand; Daniel C. Mograbi; Jesus Landeira-Fernandez; Jerson Laks; Marcia Cristina Nascimento Dourado (Arquivos de Neuro-Psiquiatria)
ABSTRACT Objective: We adapted the MacArthur Competence Assessment Tool for Treatment (MacCAT-T) to Brazilian Portuguese, pilot testing it on mild and moderate patients with Alzheimer's disease (AD). Methods: The cross-cultural process required six steps. Sixty-six patients with AD were assessed for competence to consent to treatment, global cognition, working memory, awareness of disease, functionality, depressive symptoms and dementia severity. Results: The items had semantic, idiomatic, conceptual and experiential equivalence. We found no difference between mild and moderate patients with AD on the MacCAT-T domains. The linear regressions showed that reasoning (p = 0.000) and functional status (p = 0.003) were related to understanding. Understanding (p = 0.000) was related to appreciation and reasoning. Awareness of disease (p = 0.001) was related to expressing a choice. Conclusions: The MacCAT-T adaptation was well-understood and the constructs of the original version were maintained. The results of the pilot study demonstrated an available Brazilian tool focused on decision-making capacity in AD.